AGRICULTURAL METEOROLOGY TERMS 2019–2020 AGRICULTURAL YEAR FROM DATA OF WEATHER-STATION UMAN - Novak V. G. (Uman National University of Horticulture, 2021)
According to the actual observations of weather conditions, which were held at the meteorological station Uman, by mathematical processing of data and its analysis on the basis of long-term values (avarage for 30 years - from 1961 till 1990), agrometeorological characteristics of 2019–2020 agricultural year was presented. A characteristic feature of this year was the increased temperature background, scarcity of rainfall in summer and air-soil drought, which began in June and continued until the end of summer. The average atmospheric temperature of the agricultural year amounted 10,8 °C, it was by 3,4 °C higher than the long-term average. In the cold season (December - March) sum excess was 23°C, and for the warm season (April - September) 11,7 °C. The total rainfall for the year – 415,4 mm, it is on 217,6 mm less than normal. Therefore, the long-term summer rainfall defi cit was a limiting factor for plants growth and development.